KESULITAN MEMBACA DAN MENULIS PADA SISWA BERKESULITAN BELAJAR DI KELAS TINGGI SD NEGERI BOJONG BARU - Tia Amaliah; Sundawati Tisnasari; Sigit Setiawan (STKIP Persada Khatulistiwa Sintang, 2023)
This study aims to describe reading and writing difficulties, factors that cause reading and writing difficulties, as well as teachers' efforts to help students who experience reading and writing difficulties in high grades in grade IV students at SDN Bojong Baru. The research was carried out using a qualitative approach with the subjects being fourth grade students at SDN Bojong Baru. Data was collected through observation, documentation and interviews. Data analysis is carried out through data reduction, display and verification. Based on the research results, it can be concluded that the forms of reading and writing difficulties in students with learning difficulties in high grades are disfluency in reading, errors in reading, deficiencies in visual memory, difficulty understanding sound symbols, illegible writing, late writing, missing or inverted letters and error in holding a pencil. The factors for difficulty in reading and writing are internal factors including hereditary factors, interest in reading and writing factors and motivation factors, while external factors include existing facilities at school and the family environment or where students live. Efforts made by teachers when dealing with students who have difficulty reading and writing, namely by providing remediation, using various learning media and reading and writing learning programs for students who are not yet fluent in reading and writing, especially in high classes, must be held in every school.